Transformasi Digital Pengelolaan Dokumen Fabric untuk Memaksimalkan Kualitas Layanan Gudang Berikat PT. Sunjaya Mentari Abadi - Noni Fitri Febriana; M Aji Luhur Pambudi; Atria Maharani (Politeknik bumi Akpelni, 2025)
This research examines the crucial role of bonded warehouses in the international trading system, with a case study at PT Sunjaya Mentari Abadi in Semarang. Motivated by technological developments and globalization that have pushed the international trading system to become more open, this study aims to analyze challenges in import management and document processing in bonded warehouses and formulate strategies for service quality improvement. Using a qualitative descriptive research method through in-depth interviews with management, direct observation, and documentation studies, this research reveals various challenges faced, both internal such as poor inventory management and limited trained human resources, and external such as regulatory changes and coordination barriers with stakeholders. The research findings indicate a gap between ideal conditions and operational realities that impacts service performance decline, marked by increased administrative costs, longer waiting times, and declining stakeholder trust. In conclusion, a comprehensive strategy encompassing operational process optimization, human resource competency enhancement, and technology implementation is needed to improve bonded warehouse service quality, which is not only important for maintaining competitiveness but also for ensuring smooth distribution of goods in the global supply chain.